The survival of the Varemba cultural practices in Zvishavane district-Zimbabwe (1890-2016) - Shumba, Henry Kudakwashe (Midlands State University, 2017)
The study‘s main aim is to demonstrate how the Varemba people preserved their cultural activities and to unpack the reasons behind the survival of the Varemba cultural practices in Zvishavane district. The Varemba ethnic group is a distinct group in Zvishavane, this is due to their unique way of life, their cultural practices includes Komba initiation rite, Murundu, virginity testing, testing for fertility, Female genital Mutilation (FGM), Child marriages, and inheritance. Komba is an initiation school for girls and Murundu is a school for boys and the Varemba people always attends these initiations and they serve to pass their tradition from one generation to the other, thus the survival of the Varemba cultural practices in Zvishavane district. Varemba culture survives due to the fact that it had been hidden in secrecy; therefore it has not been pervaded. There are various reasons for the survival of Varemba cultural practices and these include formation of alliances with emergent powers, acquiring higher post in their communities for instance becoming the Members of Parliament in the Varemba ethnic group and creation of their dynasties such as the Mposi dynasty. Many tribes’ cultural practices were washed away by colonialism but for the Varemba this was not the case due to various factors such as geographical location, the observance of strict endogamous way of life and the nature of the Varemba cultural practices. The Varemba ethnic groups make use of their medical knowledge to earn respect from other tribes and they managed to influence other groups to adopt their own religious practices and this preserved the Varemba cultural practices. There is lot of criticisms which were put forward by many local and international organizations concerning the Varemba cultural practices but it did not whip away their cultural practices. Thus, the survival of the Varemba cultural activities due to the fact that all the police which were introduced was not efficient.